USE OF JAVANESE VOCABULARY NGAPAK IN INDONESIAN CODE MIXING - Adjie Rangga Yasa; Nuny Sulistiany Idris; Ida Widia (RADJA PUBLIKA, 2024)
The Use of Ngapak Javanese Vocabulary in Indonesian Code Mixing.This qualitative phenomenological study examines Javanese Ngapak-Indonesian code mixing in everyday interactions in Central Java. Through observation and transcription of native speaker conversations, it was found that the integration of Ngapak vocabulary not only enriches the linguistic dimension, but also becomes an expression of cultural identity and social adaptation. This phenomenon is relevant in various domains (home, market, office, digital) and has implications for BIPA learning, where understanding code mixing improves learners' communicative competence. This finding confirms the role of regional languages ​​in maintaining Indonesia's cultural diversity in the era of globalization.